Sex and age specificities of the dynamics of anthropometric indicators characterizing obesity (according to a prospective epidemiological research) - D. P. Tsygankova; E. D. Bazdyrev; O. V. Nakhratova; I. M. Tsenter; T. F. Gaziev; E. V. Indukaeva; G. V. Artamonova; O. L. Barbarash (Acta Biomedica Scientifica, 2024)
Background. Overweight and obesity significantly increase the risk of premature death and the development of chronic diseases. Many anthropometric indices have been developed to verify obesity, although the best among them still remains undetermined.The aim. To determine the sex and age specificities of the dynamics of anthropometric indicators characterizing obesity.Materials and methods. The program was implemented in the period from 2015 to 2020. It provided for the implementation of a sample research. The baseline research included 1,124 women and 476 men. The average age was 54.9 ± 9.75 years and 52.6 ± 10.0 years, respectively. To identify gender specificities, all participants were divided into three age groups: 35–49 years old, 50–59 years old, and 60–70 years old. The observation period was 3 years. To determine the level of visceral fat, the VS-532 fat mass analyzer (Tanita Health Equipment HK Ltd., Hong Kong) was used. Body mass index (BMI), waist-hip index (WV/HV), visceral obesity index (VOI) were also calculated. Statistical processing of the results was carried out using the program Statistica 6.0 (StatSoft Inc., USA).Results. New cases of obesity developed in 30.6 % of the surveyed. There was an increase in the prevalence of obesity according to the criteria of WV (by 8.9 %) and VFL (by  5.4  %) and a  decrease in the number of people who are obese according to WV/HV – by 4.2 %. Of all the indicators, only VOI showed a statistically significant decrease in the mean values over the observed period, while BMI, WV and VFL showed an increase.Conclusions. It is necessary to apply various criteria for the diagnosis of obesity, since individual indices are not able to fully reflect the gender and age specificities of the distribution of fat in the body